Newspaper coverage and some aspects of policy in border trade union struggles - Opassi, Oskar (Annales. Series historia et sociologia, 2022)
The article details the press coverage of the general strike that took place in Trieste in June 1968 and the work stoppage at Port of Koper in March 1970. It shows the ways in which the workers’ protests were covered by the local press on both sides of the border and the social impact of the workers’ demands. It also highlights the cross-border alliances in place for the duration of the strikes in question, both in the media and in politics.
Keywords: Adriatico nord-orientale; copertura mediatica; dock workers; Koper; lavori portuali; lotte sindacali; Luka Koper; mediji; North-Eastern Adriatic; Port of Koper; Porto di Capodistria; press coverage; pristanišča; scioperi; sindikati; stavke; strike; trade union struggles; Trieste; Trst